Pressurizer Simulator - Andri Gautama Suryabrata; Tatang Mulyana; Deden Witarsyah (IAES Indonesia Section, 2015)
A dynamic two-phase imbalance mechanism model ofpressurizer in pressurized water reactor (PWR) nuclear powerplant was built based on some reasonable simplifications andbasic assumptions. The equations of energy and massconservation are used in obtaining a mathematical model forpressurizer operation. The pressurizer is divided into tworegions, steam region and liquid region but not necessary inequilibrium with each other. Considering the influence of thespray flow, surge flow, safety valve and heater, the model ofpressurizer pressure control system is established byMATLAB/Simulink in this paper. For the large overshoot,response delay and poor stability exist in the pressurizer pressurecontrol system, an advanced model based on PID controlalgorithm is proposed. The simulation results were comparedbetween two different data obtained by foreign PWR nuclearpower plant simulator. All the compared data are quite similar insimulation result, hence it proves the simulation result quiteaccurate and yet the mathematical model obtained has proved itsworking principles successfully.